Procrastination: Theoretical Review - Atalaya Laureano, Candy (2020)
The objective of this article is to analyze the current perspectives on the concept of procrastination, its types and its theoretical models which can support the variable we are talking about. Performing a systematic review of the literature about it, likewise, there were selected articles, research reports and psychometric studies published in scientific journals of psychology indexed national and international level at electronic database. The results show multiple meanings to define exactly the meaning of procrastination, its types, its theoretical models and the prevention strategies in the educational field. Finally, it concludes that through a substantial theoretical revision, it was obtain an actual concept to the comprehension of the variable under study.